1972
DOI: 10.2190/591l-7ftx-lrqt-lcue
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Care: In Hospital or at Home?

Abstract: This study was carried out, first, to determine the feasibility of postoperative home care for three elective operations and, second, to explore the feasibility of introducing postoperative home care as a more economical alternative for the following surgical procedures: herniorrhaphy, vaginal hysterectomy, and vein stripping. Clinical, environmental, operative, and socioeconomic criteria were applied to 487 outpatients of which 44 pairs were selected and matched by age, sex, diagnosis, environmental, and soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1980
1980
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…Of the 34 studies in which any cost data were presented, 32 concluded that HITH care was cheaper 12 . ‐ 16 , 23 , 24 , 27 29 , 33 36 , 40 ‐ 43 , 46 , 48 , 49 , 51 , 53 , 55 , 59 ‐ 64 , 69 , 70 The other two studies concluded that hospital care was cheaper 40 , 71 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 34 studies in which any cost data were presented, 32 concluded that HITH care was cheaper 12 . ‐ 16 , 23 , 24 , 27 29 , 33 36 , 40 ‐ 43 , 46 , 48 , 49 , 51 , 53 , 55 , 59 ‐ 64 , 69 , 70 The other two studies concluded that hospital care was cheaper 40 , 71 .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 34 studies in which any cost data were presented, 32 concluded that HITH care was cheaper. [12][13][14][15][16]23,24,[27][28][29][33][34][35][36][40][41][42][43]46,48,49,51,53,55,[59][60][61][62][63][64]69,70 The other two studies concluded that hospital care was cheaper. 40,71 Overall, the cost for HITH care was 73.5% of the average for the control groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A pesar del auge de estas instituciones, la revisión de la literatura muestra que, a la fecha, no se ha desarrollado ninguna investigación que permita caracterizar los retos y requerimientos logísticos que enfrentan los administradores de servicios de HHC. Solo un trabajo presenta la implementación de estos servicios en el departamento del Valle del Cauca desde una perspectiva médica (Echeverri, Manzano, Gomez, Quintero y Cobo, 1972). Estos hechos evidencian la necesidad de caracterizar e identificar la gestión logística en la prestación de servicios de HHC en el contexto nacional y regional, para contribuir en la disminución de la brecha entre el estado del arte y la realidad de la prestación de los servicios en dicho contexto.…”
Section: Introductionunclassified